2021
DOI: 10.1002/dev.22162
|View full text |Cite
|
Sign up to set email alerts
|

Increase in sexual motivation throughout adolescence in the cycling female rat

Abstract: Sexual behavior in the female rat is a highly motivated behavior first displayed during adolescence, a developmental period when neural circuits underlying motivation are not mature. This study characterizes the natural development of sexual motivation and behavior of female rats. We compared the incentive value of the male for mid‐adolescent (PNDs:39‐43), late adolescent (PNDs:49‐53), and adult (PNDs:90‐115) cycling females, using a male–female preference task and an ultrasonic vocalization emission test foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…However, there has been controversy regarding the importance of male calls in female mate choice; while some studies support the importance of male calls (Thomas and Barfield, 1985 ; Gerson et al, 2019 ) eliciting female approach behavior (Seffer et al, 2014 ; Willadsen et al, 2014 ; Berg et al, 2018 , 2021 ; Kisko et al, 2018 , 2020 ), others found that females choose vocalizing vs. non-vocalizing males equally often (Snoeren et al, 2014 ). Despite the contradictory results, it is well accepted that female rats emit more calls when interacting with male vs. female conspecifics (White et al, 1993 ; Armas et al, 2021 ), probably signaling sexual motivation towards the male (Börner et al, 2016 ) and that male USVs can trigger female solicitation behavior (McIntosh et al, 1978 ), including ear wiggling and darting behavior. Solicitation behaviors seem to be rewarding for both sexes (Martínez and Paredes, 2001 ) and increase male sexual arousal, hence activating male mounting behavior with a shorter latency (Chu and Ågmo, 2015b ; Ågmo and Laan, 2022 ) and pointing to a certain choice from the male towards the female.…”
Section: Contribution Of Ultrasonic Vocalizations To the Evaluation A...mentioning
confidence: 99%
“…However, there has been controversy regarding the importance of male calls in female mate choice; while some studies support the importance of male calls (Thomas and Barfield, 1985 ; Gerson et al, 2019 ) eliciting female approach behavior (Seffer et al, 2014 ; Willadsen et al, 2014 ; Berg et al, 2018 , 2021 ; Kisko et al, 2018 , 2020 ), others found that females choose vocalizing vs. non-vocalizing males equally often (Snoeren et al, 2014 ). Despite the contradictory results, it is well accepted that female rats emit more calls when interacting with male vs. female conspecifics (White et al, 1993 ; Armas et al, 2021 ), probably signaling sexual motivation towards the male (Börner et al, 2016 ) and that male USVs can trigger female solicitation behavior (McIntosh et al, 1978 ), including ear wiggling and darting behavior. Solicitation behaviors seem to be rewarding for both sexes (Martínez and Paredes, 2001 ) and increase male sexual arousal, hence activating male mounting behavior with a shorter latency (Chu and Ågmo, 2015b ; Ågmo and Laan, 2022 ) and pointing to a certain choice from the male towards the female.…”
Section: Contribution Of Ultrasonic Vocalizations To the Evaluation A...mentioning
confidence: 99%
“…As this variable is sensitive to hormonal treatments that modify the sexual motivation of females [89][90][91][92], we evaluated the incentive value of the male for adolescent and adult rats in two motivational tests: a male vs. female preference task [45] (Figure 2A) and 50 kHz USV emission after a brief sexual vs. social interaction [74] (Figure 2B). Interestingly, mid-adolescent rats exhibited a reduced preference for the male compared to adults, and unlike females in later developmental stages, did not perform a greater number of attempts to access the male in this test [45,88]. In addition, these young sexually active females did not increase the emission of 50 kHz USV after a brief interaction with a male relative to an interaction with a female, as late-adolescent and adult rats did [88].…”
Section: Adolescence: the Developmental Period When The Female's Sexu...mentioning
confidence: 76%
“…Despite the lack of differences in proceptive responses and lordosis quotient between these age-groups, the intensity of the lordosis response (how pronounced the dorsiflexion is [89]) was reduced in mid-adolescent females [88]. As this variable is sensitive to hormonal treatments that modify the sexual motivation of females [89][90][91][92], we evaluated the incentive value of the male for adolescent and adult rats in two motivational tests: a male vs. female preference task [45] (Figure 2A) and 50 kHz USV emission after a brief sexual vs. social interaction [74] (Figure 2B).…”
Section: Adolescence: the Developmental Period When The Female's Sexu...mentioning
confidence: 78%
See 1 more Smart Citation
“…It is also possible that the overall reduction in ambulation by MC4RKO mice impacted their frequency of approaching the male (although see discussion of the behavior of tbMC4R oxt mice below). Additional experimental designs used in rats to gauge female sexual motivation should be employed in future studies, such as social approach chambers comparing interest in intact and gonadectomized males, paced mating chambers, measurement of ultra-sonic vocalizations, conditioned place preference studies, or operant chambers to assess the number of nose pokes a female will exhibit to gain access to a male (67,68).…”
Section: Melanocortins and The Female Sexual Responsementioning
confidence: 99%